Chemo-Immunotherapy Regimes for Recurrent or Metastatic Nasopharyngeal Carcinoma: A Network Meta-Analysis and Cost-Effectiveness Analysis - Zhu, Youwen; Liu, Kun; Ding, Dong; Wang, Kailing; Liu, Xiaoting; Tan, Xiao (Frontiers in Pharmacology, 2022)
Introduction: In 2021, two phase III clinical trials confirmed that toripalimab or camrelizumab combined with gemcitabine and cisplatin (TGP or CGP) provide more benefits in the first-line treatment of R/M NPC than GP. Fortunately, TGP and CGP were recently approved as first-line treatments for cases experiencing R/M NPC by the China National Medical Products Administration in 2021. However, due to the high cost and variety of treatment options, the promotion of chemo-immunotherapeutics in the treatment of R/M NPC remains controversial. Therefore, we performed a cost-efficiency assessment of the two newly approved treatment strategies to assess which treatments provide the greatest clinical benefits at a reasonable cost. Methods: A Markov model was expanded for the evaluation of the effectiveness and cost of TGP, CGP, and GP chemotherapy with a 10-year horizon and measured the health achievements in quality-adjusted life-years (QALYs), incremental cost-effectiveness ratios (ICERs), and life-years (LYs). We constructed a treatment strategy and other parameters based on two clinical trials and performed one-way and probabilistic sensitivity experiments for the evaluation of the uncertainty in the model. Results: For the model of patients with treatment-R/M NPC, TGP was associated with a total cost of $48,793 and 2.895 QALYs (5.217 LYs), leading to an ICER of $9,423 per QALY ($5,653 per LY) compared to CGP. On comparing the GP chemotherapy, we found TGP and CGP incurred substantial health costs, resulting in ICERs of $18,052 per QALY and $20,478 per QALY, respectively. The risk of adverse events (AEs) and the price of the drugs had significant impacts on the ICER. At the assumed willingness-to-pay (WTP) threshold of $35,673 per QALY, there were approximately 77.4% and 68.9% simulations in which cost-effectiveness was achieved for TGP and CGP, respectively. Conclusion: From the Chinese payer's perspective, TGP is more possible to be a cost-effective regimen compared with CGP and GP for first-line treatment of patients with R/M NPC at a WTP threshold of $35,673 per QALY.